Supernatants from Newly Isolated Lacticaseibacillus paracasei P4 Ameliorate Adipocyte Metabolism in Differentiated 3T3-L1 Cells - Natalia Grigorova; Zhenya Ivanova; Valeria Petrova; Ekaterina Vachkova; Georgi Beev (Biomedicines)
Background: Lacticaseibacillus paracasei (L. paracasei) strains and their postbiotics show potential for managing metabolic disorders such as diabetes and obesity. Two newly isolated L. paracasei strains, M2.1 and P4, were yielded from Formica rufa anthills in Sinite Kamani National Park, Bulgaria. Their metabolic effects on mature 3T3-L1 adipocytes were investigated. Methods: Mature 3T3-L1 adipocytes were treated for 24 h with 10% (v/v) cell-free supernatants (CFSs) of M2.1 or P4. Two experimental (M2.1, P4) and two control groups (mature, untreated adipocytes and mature adipocytes, treated with 10% (v/v) MRS broth) were analyzed for intracellular lipid accumulation, glucose uptake, and the mRNA expression of lipid metabolism and beta-oxidation-related genes. Fold changes in gene expression were assessed using RT-qPCR. Results: Both M2.1 and P4 CFSs enhanced glucose uptake by over 30% compared to the control. P4 demonstrated a more favorable effect by significantly upregulating adipose triglyceride lipase–patatin-like phospholipase domain containing 2, adiponectin, and peroxisomal beta-oxidation enzymes—acyl-coenzyme A oxidase 1, palmitoyl. Intracellular lipid accumulation increased only with M2.1, while P4 supported improved lipid turnover without promoting excessive lipid storage or lipolysis. Conclusions: P4 CFS exhibits the potential to improve adipocyte metabolism by enhancing glucose uptake, promoting beta-oxidation, and increasing adiponectin expression, offering a promising strategy for managing metabolic dysfunctions.